Phycoremediation of NH4+ and PO43- from meat processing wastewater by using microalgae botryococcus sp. - Shanmugan, Vikneswara Abirama (2017)
Phycoremediation is purposed to remove or biotransformation of pollutants including nutrients from wastewater. The excessive content of nutrients in a water body will lead to high concentration of undesirable microorganisms such as phytoplankton. This will lead to more serious problems that affects the ecosystem and brings human health problems. In over many years ago, considerable researches have been carried out on use of microalgae in wastewater treatment but the effect on particular type of wastewater discharged from meat processing industry is less reported. Wastewater disposed from meat processing industry has high content of NH4+ and PO43-. Hence, this study is carried out to determine the effectiveness of microalgae Botryococcus sp. to remove nutrients NH4+ and PO43- from wastewater from meat food processing industry and establishes the characteristic of this wastewater. Five concentrations of Botryococcus sp., 1x103, 1x104, 1x105, 1x106 and 1x107 cell/ml were cultivated with three samples of wastewater which are sample obtained at two peak hours, 9.00 a.m. and 12.00 p.m. and composite sample of wastewater obtained hourly from 8.00 a.m.-5.00 p.m. (the factory working hour). The sample obtained at 9.00 a.m. contains highest BOD, COD, TSS, NH4+ and PO43- compared to 12.00 p.m. and composite samples. For the removal of NH4+ and PO43-, the best microalgae concentration is 1x106 cell/ml in which removal efficiency of NH4+ and PO43- achieved 89.74-99.03% and 92.39-99.93% respectively. Factors affecting the Botryococcus sp. growth are also studied and found that pH 7, N:P ratio 2:1 and initial Botryococcus sp. concentration of 106 as the optimized factors. Biokinetic coefficients of NH4+ removal by Botryococcus sp. were determined as reaction rate constant,